Does financial innovation enhance financial deepening and growth in Kenya? - Roseline Nyakerario Misati; Jared Osoro; Maureen Odongo (Kenya Bankers Association (KBA), 2021)
This study examined the implication of financial innovation on financial depth and economic growth in Kenya using quarterly data covering the period 2009 to 2020. Based on autoregressive distributive lag models, we demonstrate a positive relationship between financial innovation and financial depth with the strongest impact emanating from internet usage and mobile financial services and the lowest impact from the number of bank branches and automated teller machines. The results also further reveal a significant positive impact of financial depth on economic growth consistent with the supply-leading finance theory. The study recommends investment in technology-enabling infrastructure for digital financial services, design strategies to ensure affordability of mobile devices and prioritisation of financial literacy to bridge the gap between people and technology.
Keywords: 330; Financial Innovation; Financial Depth; Growth